COOPERATIVE ACCOUNTING TRAINING FOR ONE-HEARTED PARENT WASTE BANK COOPERATIVES - Etty Murwaningsari; Deni Darmawati; Sofie Sofie; Yvonne Augustine; Diana Frederica (Jurnal Scientia, 2023)
The implementation of PKM activities with the theme "Cooperative Accounting Training for the One Heart Waste Bank Cooperative" aims to increase the understanding of cooperative management in implementing cooperative accounting. The understanding of cooperative accounting needs to be improved because the application of cooperative accounting will be able to provide benefits, both in managing cooperative businesses and for external stakeholders. The main topics of discussion in this PKM activity include the accounting cycle, types of cooperative financial reports, and the required accounting. At the beginning of the session, a pre-test will be conducted and at the end of the session a post-test will be conducted to measure an increase in the understanding of cooperative management towards cooperative accounting. The implementation of this PKM is in collaboration with PKM Cooperative partners for the Satu Hati Waste Bank. The cooperative is located at Jl. Kemuning Raya Rt. 005/05 Ex. Cengkareng Barat, Kec. Cengkareng – West Jakarta. It is hoped that this PKM activity can continue to be carried out to increase understanding of Cooperative Accounting.